250 Analysten, 1 Portfolio? - Dornau, Robert,Szczesny, Andrea (ZEW, 1999)
This study analyzes portfolio recommendations of financial experts, finding significant differences in portfoliostructure depending on the experts' institutional background. The recommendationsystem from a survey of 250 financial experts from banks, insurance companies, investment funds and industrial enterprises. The respondents were asked to construct a portfolio of retirement savings using the following assets: European and foreign stocks and bonds, real estate and money market funds. The main differences in asset allocation are found for the shares of European stocks and real estate. Five portfolios constructed from the recommendations are compared using different performance and risk measures.
Zsfassung in engl. Sprache
Keywords: Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Altersvorsorge; Portfolio-Management; Anlageberatung; Rendite; Vergleich; Schätzung; Deutschland